The Challenges of Green Marketing Communication: Effective Communication to Environmentally Conscious but Skeptical Consumers - Carmen Grebmer; Sarah Diefenbach (Designs, 2020)
Effectively communicating properties of environmental products to consumers can be challenging. This especially pertains to highly environmentally conscious (HEC)—yet skeptical—consumers, since this target group must balance the need for reliable product knowledge with high sensitivity to often ambiguous nonverbal cues about a product’s environmental friendliness (e.g., environmental pictures). Using a group-specific (2 ×) 2 × 2 repeated-measures experimental study, we investigated the effect of communication-channel-specificity (verbal and nonverbal) to convey the environmental friendliness of products and evaluated consumers’ environmental skepticism and attention during product presentation. Environmental information delivered via a verbal/text-based communication channel translates into low skepticism for both HEC and low environmental consciousness (LEC) consumers. However, nonverbal/pictorial communication proved persuasive only for LEC consumers; HEC consumers exhibited high levels of skepticism, which, in turn, decreased the products’ perceived environmental friendliness. The analysis of combined verbal and nonverbal communication presented here provides a promising framework for effective green marketing communication.